Impact of emotional intelligence on the success of startups in business incubators - De-Esteban-Escobar, Débora; De-Pablos-Heredero, Carmen; Montes-Botella, José Luis; Blanco-Jiménez, Francisco José (Frontiers in Organizational Psychology, 2025)
IntroductionThis research investigates the impact of business incubators' training and support initiatives on emotional intelligence in entrepreneurship and how this subsequently affects the success of incubated startups.MethodsThe study proposes and tests four hypotheses using a structural equation model (SEM) and data collected from October 2023 to February 2024.ResultsThe findings indicate the following: First, business incubator training programmes significantly enhance entrepreneurs' emotional intelligence. Second, psychological support services help entrepreneurs overcome challenges and maintain a positive mindset. Third, incubators provide a supportive environment that fosters entrepreneurs' confidence, contributing to business success.DiscussionBy elucidating the relationship between incubator activities, emotional intelligence development, and entrepreneurial success, this study can inform the design of more effective business incubator programmes and the development of policies prioritising entrepreneurs' emotional growth, strengthening the entrepreneurial ecosystem.